Modeling, development and validation of environmental behavior scale for preservice teachers - Ece Avinç; Fatih Doğan (Scientific Reports)
Abstract This research aimed to formulate a robust and valid measurement instrument for evaluating the environmental behavior levels of prospective teachers. The study focused on detailing the analyses conducted on the Environmental Behavior Scale (EBS). Content validity was ascertained through expert assessment, while construct validity investigations were aligned with the Theory of Planned Behavior (TPB). Employing both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), the study involved teacher candidates from a Faculty of Education. EFA findings proposed an 18-item, five-factor model. This model was subsequently cross validated through CFA, exhibiting favorable fit indices. Structural Equation Modeling (SEM) was applied to unveil relationships among variables, indicating positive cognitive, affective, and behavioral responses to environmental concerns among teacher candidates. The measurement invariance of the SEM model was examined in terms of the gender variable, and it was found that the model did not change. Consequently, EBS emerges as a valuable tool for environmental education, offering insights into variables such as attitude towards behavior, perceived behavioral control, subjective norm, behavioral intention, and actual behavior in teacher candidates.